HUBUNGAN DAN IMPLIKASI ANTARA SUPERVISI PENDIDIKAN DENGAN KINERJA GURU PADA SMA YOS SUDARSO MEDAN - Aditia Hizki Pranata Tarigan Tambak; Berlianta Saragih; Enjel Mitra Wati Hulu; Meiriati Simanjuntak; Yuda Sanrico Manullang; Anugrah Setiawan (CV. Adiba Aisha Amira, 2025)
This study aims to examine the relationship and implications between educational supervision and teacher performance at SMA Yos Sudarso Medan. The research is grounded in the importance of the teacher’s role in improving the quality of education and the need for effective strategies to support teacher professionalism, one of which is through educational supervision. Supervision functions as a systematic mentoring and guidance tool to assist teachers in planning, implementing, and evaluating the learning process more effectively. This study employs a descriptive qualitative approach, with data collected through interviews and observations. The findings reveal a strong correlation between educational supervision and improved teacher performance. Consistent and effective supervision practices at SMA Yos Sudarso have had a positive impact on teachers’ abilities in lesson planning, classroom management, and reflective teaching practices. The implications of these findings indicate that supervision serves not only as a monitoring tool but also as a strategy for continuous professional development, contributing to the realization of higher quality education.